Surgical Valvuloplasty Versus Balloon Dilation for Congenital Aortic Stenosis in Pediatric Patients. Issue 4 (July 2020) - Herrmann, Jeremy L.; Clark, Aaron J.; Colgate, Cameron; Rodefeld, Mark D.; Hoyer, Mark H.; Turrentine, Mark W.; Brown, John W.
Background: For children with congenital aortic stenosis (AS) who are candidates for biventricular repair, valvuloplasty can be achieved by surgical aortic valvuloplasty (SAV) or by transcatheter balloon aortic dilation (BAD). We aimed to evaluate the longer term outcomes of SAV versus BAD at our institution. Methods: We retrospectively reviewed the outcomes of 2 months to 18 years old patients who underwent SAV or BAD at our institution between January 1990 and July 2018. Baseline and follow-up characteristics were assessed by echocardiography. Long-term survival, freedom from reintervention, freedom from aortic valve replacement (AVR), and aortic regurgitation were evaluated. Results: A total of 212 patients met inclusion criteria (SAV = 123; BAD = 89). Age, sex, aortic insufficiency (AI), and aortic valve gradient were similar between the groups. At 10 years, 27.9% (19/68) of SAV patients and 58.3% (28/48) of BAD patients had moderate or worse AI ( P = .001), and reintervention occurred in 39.2% (29/74) of SAV patients and 78.6% (44/56) of BAD patients ( P < .001). Kaplan-Meier analysis revealed overall survival was 96.8% (119/123) for SAV and 95.5% (85/89) for SAV ( P = .87). At 10 years, 35% (23/66) of SAV patients and 54% (23/43) of BAD patients underwent AVR ( P = .213). Conclusions: Surgical aortic valvuloplasty demonstrated greater gradient reduction, less postoperative and long-term AI, and a lower reintervention rate at 10 years than BAD. There was no difference in survival or AVR reintervention rate. Surgical aortic valvuloplasty is a durable and efficacious intervention and should continue to be considered a favorable choice for palliation of valvular AS.